The Influence of School Environment on Students' Learning Interest at the MTS Level - Arifin, Samsul; Zidan Rafsanjani, Moh. (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to analyze the influence of the school environment on the learning interest of students at the junior high school level, namely MTs. The development of the world of education in all aspects includes; Learning materials, access to education, educational facilities, all of these things should be balanced with an increase in students' interest in learning, but the facts found in the field are still lacking in the level of interest in learning. This study intends to find out how the school environment affects students' interest in learning in MTs. This study uses a qualitative method with a literature study approach that includes various literature studies, articles, journals and theses related to the research object. The results of the study show that the school environment has a positive effect on students' interest in learning, an effective and efficient learning environment can increase students' interest in learning, and the optimization of a more adequate learning environment will support the learning process so that students' interest in learning will increase.